(3GdeOGQcs - (3GdYGedj, GdehShj, GdLYHj, eMeO Hf Ydj Hf MSjf, J (B1009 (3g`s ((3eMeO WGgQ GdbRhjfjs)
(3ChdgG (B:s
(3GdMeO ddg (B... (3bhdg bOS Gddg SQg hWgQ QeSg (B: (3cJGH GdWgGQI ; GdcJGH eUOQ KGdK dcJH ef GdcJH hgh GdLeY bGd LeY ef GdeaSQjf GdeQGO Hbhdg JYGdi (B{ (3ChdFc cJH aj bdhHge GdEjeGf (B} ...s
(3BNQgG (B:s
...(3bhdg GdSGHYI EPG ONd hbJ fGadI GdRhGd ade jUd hSGaQQGSJMH dg bVGDg hdh aj GdSaQ GdeQGO (B.. (3Cfg bGd GdUdGI aj GdSaQ QcYJGf djS bHdgeG TjF hdG HYOgeG TjF (B. (3Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf (B3\507s
(3gOjI GdYGQajf (B2\264s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis